CULTURAL HERITAGE AND COLLABORATIVE URBAN REGENERATION: THE SANSEVERO CHAPEL MUSEUM FOR THE HISTORIC CENTRE OF NAPLES - Clemente, Massimo; Castagnaro, Alessandro; Oppido, Stefania; Daldanise, Gaia (BDC. Bollettino Del Centro Calza Bini, 2015)
Cultural heritage has played a key role in urban regeneration processes although often with negative effects, such as the museification and gentrification of historic centres. The ancient centre of Naples is an emblematic case study because deeply degraded but strongly characterised by cultural identity. In the area, the Sansevero Chapel is a private museum very appreciated by tourists visiting Naples and famous for its historical heritage. Since the 90s, the museum is developing an innovative policy, playing an active role in the urban regeneration; on one hand, it increased its cultural activities, on the other hand, it promoted the valorization of the urban area interacting with stakeholders and involving local community, especially supporting the initiative of “Corpo di Napoli” Committee. Starting from the case study, the paper aspires to offer useful insights for collaborative models of urban regeneration in historic centres. Keywords: cultural heritage, historic centre, collaborative urban regeneration